Perempuan Difabel Berhadapan Hukum - Muhammad Julijanto (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper describes women with disabilities who are facing legal cases, most of which are related to cases of sexual violence. The handling of cases of women with disabilities experienced problems, namely: law enforcers did not have a maximum understanding of the disabled; 2) limited access; 3) limited evidence: 4) difficulty communicating; 5) the community does not want to be a witness; 6) length of legal process; 7) lack of knowledge about the law; 8) there is no assistance in the police department during inspections, the examination room is not easily accessible, and the lack of information for victims; 9) the prosecutor does not provide information if the file has been delegated and; 10) judges have difficulty communicating. Therefore, law enforcers must have the same perception of diffables, so that they get legal justice.